IDENTIFIKASI CERITA ANAK BERBASIS BUDAYA LOKAL UNTUK MEMBUDAYAKAN LITERASI DI SD - Isnaeni Wahab (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2019)
Local culture is the identity of an area where in this era its features are increasingly eroded by foreign cultures. It happened because of the ease with which foreign cultures enter and blend in with local cultures which can directly affect the cultural structure of the nation. Likewise with folklore as if forgotten. Folklore is one of the national cultural heritages which is a national honor with a diverse culture that must be introduced to students since elementary school. This study aimed to identify the children's stories based on local culture and implement literacy culture at SD Kartika XX-I Makassar. The approach used in this research was descriptive qualitative with survey method while the data collection techniques used were observation, documentation, interviews and questionnaires. Based on the data obtained, the researchers identified twelve children's story titles which were then carried out by literacy to elementary students of Kartika XX-I Makassar. The application of literacy culture in SD Kartika XX-1 Makassar by 1) distributing story books to students 2) reading about 15-20 minutes, 3) students identifying moral values ​​contained in the story, 4) strengthening the moral values ​​of the story children and the application of local culture in accordance with national values.